Peran Local Champion Dalam Pengembangan Pariwisata Berbasis Komunitas Di Balkondes Tuksongo, Wringinputih, dan Giritengah - Ardian Indro Yuwono; Herni Putrianti (JURNAL DESTINASI PARIWISATA, 2022)
Community leaders or local champion have important role for develop tourist villages andcommunity empowerment processing. Balai Ekonomi Desa (Balkondes) program is a community-basedtourism development program which implemented at villages around Borobudur. This article explains therole of government, stakeholders, and the role of local champions in mediating, facilitating and mobilizingthe community. This study used qualitative research methods through in-depth interviews using snowballtechniques. The themes emerged from this research, the role of PT.TWC is to initiate the program andconnect to BUMN as a partners to each village. The selection or presence of local champions is determinedthrough an informal process. In each village represented by one supervisor becomes a local champion whoplays an important role.Keyword: local champion; balkondes; pariwisata berbasis komunitas